2017
DOI: 10.3389/fnins.2017.00010
|View full text |Cite
|
Sign up to set email alerts
|

MEG Signatures of a Perceived Match or Mismatch between Individual and Group Opinions

Abstract: Humans often adjust their opinions to the perceived opinions of others. Neural responses to a perceived match or mismatch between individual and group opinions have been investigated previously, but some findings are inconsistent. In this study, we used magnetoencephalographic source imaging to investigate further neural responses to the perceived opinions of others. We found that group opinions mismatching with individual opinions evoked responses in the anterior and posterior medial prefrontal cortices, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
3
7
0
1
Order By: Relevance
“…The difference in performance under the influence of concurring and conflicting cues is most prominent in the 200-300 ms interval. Similar differences between conflict and no-conflict trials have been reported in recent papers (Shestakova et al, 2012;Zubarev et al, 2017). This time interval can potentially reflect an interaction between the social cues provided and the sensory information.…”
Section: Discussionsupporting
confidence: 83%
“…The difference in performance under the influence of concurring and conflicting cues is most prominent in the 200-300 ms interval. Similar differences between conflict and no-conflict trials have been reported in recent papers (Shestakova et al, 2012;Zubarev et al, 2017). This time interval can potentially reflect an interaction between the social cues provided and the sensory information.…”
Section: Discussionsupporting
confidence: 83%
“…Alternatively, the increase in MCT4 and lactate release observed here might be deleterious for the neurons, if the reported improved cognitive ability and reduced neuronal apoptosis observed in one Alzheimer’s disease mouse model after injection of siMCT4 [ 65 ] is confirmed by further studies. The increased lactate produced by reactive astrocytes may also be preferentially directed to microglia, as suggested by the recently proposed hypothesis of the astrocyte–microglia lactate shuttle (AMLS), an adaptation of the ANLS, which would take place under conditions of neuroinflammatory infectious diseases [ 66 , 67 ]. Finally, there is fast growing evidence showing that glycolysis plays a critical role in the activation of immune cells [ 68 , 69 ] and an increase in glycolytic metabolism has also been reported in inflammatory microglia (for a review, see [ 70 ]).…”
Section: Discussionmentioning
confidence: 99%
“…So, there is a theoretical possibility as well as studies also to support that sometimes they both coexist in the same patient wherein the cause is labelled as mixed. Possibly, miscellaneous causes of hyponatremia in a few previous studies as summarized here might have included mixed cases too 1 , 2 . I suggest little elaboration of the mixed cause and strategy of its management should have been included as well.…”
mentioning
confidence: 92%